In vitro study of the demineralization induced in human enamel by an acidic beverage using X‐ray fluorescence spectroscopy and Raman microscopy. (18th November 2018) - Cândido, M.; Silveira, J.M.; Mata, A.; Carvalho, M.L.; Pessanha, S.
Abstract : This study was conducted with the purpose of evaluating the demineralization effect of a widely consumed acidic soft drink, Coca‐Cola®, in human enamel. This way, an in vitro model for the daily intake of this beverage was developed taking into account the intraoral environment. The evaluation of the enamel specimens was undertaken considering two approaches, the direct analysis of enamel surface and the study of specimens as cross sections. The depolarization ratio of the phosphate symmetric stretching band in Raman spectra was used to evaluate the loss of mineralization of the hydroxyapatite matrix, and the changes regarding the elemental content was performed using energy‐dispersive X‐ray fluorescence (EDXRF). For comparison, the Rayleigh‐to‐Compton ratio in EDXRF spectra of enamel samples was also determined in order to establish alterations in the average atomic number of the samples before and after erosive challenge. Considering the model applied and the timeframe of study, we determined evidences of demineralization after consumption of this drink. There was a significant increase of depolarization ratio in most of the analyzed specimens as well as a decrease of the concentration of major elements concomitant with apparent increase of the concentration of trace elements. Moreover, depths of demineralization of tens of micrometers were obtained with both spectroscopic techniques, showing consistency between the obtained results.